Effects of infilled wall opening on load resisting capacity of RC frames to mitigate progressive collapse risk. (15th November 2020) - Qian, Kai; Lan, Dong-Qiu; Fu, Feng; Li, Bing
Highlights: Load carrying mechanisms of RC infilled frames are evaluated. Enhancement of infill walls on collapse resistance of frames is captured. Detrimental effects of openings on enhancement efficiency of infill walls are quantified. For failure mode, infill walls may change the position of rebar fracture significantly. Effects of overhanging beams on failure mode of edge columns are quantified. Abstract: To quantify the load redistribution capacity of infill walls in reinforced concrete (RC) frames to resist progressive collapse, a series of five 1/4 scaled RC frames with or without infill walls were tested. The two-bay and three-story RC frames were tested using a pushdown loading regime. It was found that the infill walls could increase the first peak load by 256%. Even with an opening ratio of 31%, the infill walls could still increase the first peak load by 88%. This could be explained as the first peak load of infilled frames was attributed into equivalent struts of infill walls while the first peak load of bare frame mainly attributed in the flexural action of the beams. Beyond expectation, infill walls may not reduce the deformation capacity of the frames and secondary short struts of the infill walls could enhance the load resistance of the frame in large deformation stage. The opening ratio of 11%, 16%, and 31% could decrease the first peak load of the infilled frames with solid walls by 13%, 25%, and 47%, respectively. Moreover, the infilled walls with or without openings may change the position of rebar fracture of the beams. Thus, it was incorrect to simplify multi-story infilled frames into single-story substructures.